Guest Satisfaction on Star Hotel Preparedness In New Normal Era of Covid-19 - Ervina, Ersy; Taufiq, Riza; Masatip, Anwari (APMBA (Asia Pacific Management and Business Application), 2021)
Implementing health protocols is one of the hotel industry's survival strategies in response to the Covid-19 pandemic. Although many studies have examined the importance of management strategies in dealing with disasters in the context of the Covid-19, there has been no study analyse the level of guest satisfaction on the preparedness of star hotels during the 'New Normal Era in Bandung, West Java. This research was conducted to evaluate guest satisfaction on star hotels' preparedness by collecting data from guests who had stayed during the pandemic. Importance-Performance Analysis (IPA) by sampling 100 respondents was used to assess guest satisfaction with performance, especially within the star hotel section, then dividing the results into four quadrants (Priority, Maintain, Low priority, and Excessive) and Guest satisfaction determine by using Customer Satisfaction Index (CSI). IPA analysis results show most of hotel section have implemented the preparedness health protocol that exceeds guests' expectations. Measurement of the guest satisfaction index shows guests are very satisfied with star hotels' preparedness in reducing the risk of the Covid-19 pandemic. However, star-hotels still need improve the preparedness by adapting and innovating service through technology.